2019
DOI: 10.1016/j.heliyon.2019.e01159
|View full text |Cite
|
Sign up to set email alerts
|

Studies of different types of insulating oils and their mixtures as an alternative to mineral oil for cooling power transformers

Abstract: Because of their availability and low cost, mineral oils have been widely used for a long time in power transformers to allow their insulation and cooling. However, their low fire safety and low biodegradability potential have made it necessary to look for other insulating liquids as an alternative to this mineral oil used in high voltage electrical equipment. This work presents an experimental study to compare between the physicochemical characteristics of mineral oil, olive oil, sunflower oil and different o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 15 publications
0
31
1
1
Order By: Relevance
“…The addition of olive oil up to 15% and of Jatropha oil up to 20% to mineral oil improves the mineral oil's performance. Recently, the dielectric properties and heat-dissipating ability of blends of mineral oil with olive oil and sunflower oil were investigated and the study confirmed the use of mixed oil for non-cold-climate regions [65].…”
Section: B Retrofilling and Miscibilitymentioning
confidence: 91%
“…The addition of olive oil up to 15% and of Jatropha oil up to 20% to mineral oil improves the mineral oil's performance. Recently, the dielectric properties and heat-dissipating ability of blends of mineral oil with olive oil and sunflower oil were investigated and the study confirmed the use of mixed oil for non-cold-climate regions [65].…”
Section: B Retrofilling and Miscibilitymentioning
confidence: 91%
“…Petroleum-based fluids and lubricants are applied as lubricants and dielectric and coolant material in electrical or electronic devices such as power systems (transformers), machinery, and the automotive and biomedical industries, among others [ 4 , 5 , 6 , 7 ]. Paraffinic and naphthenic oils are examples of mediums used for these applications [ 8 ]. Nevertheless, these materials exacerbate environmental issues due to their eco-toxicity, incomplete biodegradability, and highly probable carcinogenic characteristics [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure the secure operation of a transformer, testing procedures on dielectric quality of transformer oil have been conducted to fulfill the purpose of insulating as well as cooling. 1211 aged oil samples produced results in oil resistivity, dissipation factor, conductivity, viscosity and breakdown voltage [4]. The conducted tests have been realized in accordance with the IEC standard test procedures which are IEC 60156, IEC 60245 and IEC 61125 [4].…”
Section: Introductionmentioning
confidence: 99%
“…1211 aged oil samples produced results in oil resistivity, dissipation factor, conductivity, viscosity and breakdown voltage [4]. The conducted tests have been realized in accordance with the IEC standard test procedures which are IEC 60156, IEC 60245 and IEC 61125 [4]. In order to conduct the tests, insulating oils will be mixed in precise amounts to determine the breakdown voltage and the electrical field intensity of electro-convection.…”
Section: Introductionmentioning
confidence: 99%